Disability and political activism in industrialising Britain, c. 1830–1850. (3rd April 2022) - Turner, David M.; Blackie, Daniel
ABSTRACT: This article examines disabled people's political activism in Britain before the emergence of the modern disability rights movement (DRM). Focusing on the campaign for shorter factory working hours in the 1830s and 1840s, it highlights the centrality of so-called 'factory cripples' to the reformist cause, both figuratively and as witnesses to the consequences of industrial labour. Drawing on a wide range of sources – from accounts of campaign speeches and gatherings to official reports and the writings and testimonies of impaired workers – the article shows how the factory movement opened spaces for working-class 'maimed' and 'deformed' people to talk about their experiences in their own words. Self-proclaimed 'factory cripples' engaged in the fight for shorter hours in complex and reciprocal ways, with some using it to advance a socio-cultural understanding of 'disability'. Recognising this reminds us that disabled people engaged in significant forms of political activism long before the twentieth century and suggests that the analysis developed by the DRM was not as pioneering as some studies imply.